Determinants of Regional Government Assets Report Quality With Leadership Commitment as a Moderator In State Educational Units Under The Jakarta Provincial Education Department - Aulia, Syafrani (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze the factors influencing the quality of Regional Government Assets reports, with leadership commitment as a moderating variable. The key variables examined in this research include human resource competence, work motivation, and the use of information technology. The study population consists of asset managers in state educational institutions under the Jakarta Provincial Education Department, with a census sampling method involving all population members as respondents. Data was collected through questionnaires and analyzed using multiple regression analysis with SPSS version 26. The findings reveal that human resource competence, work motivation, and the use of information technology significantly influence the quality of Regional Government Assets reports. However, leadership commitment does not moderate the relationship between human resource competence and work motivation in determining report quality. In contrast, leadership commitment does moderate the impact of information technology use on Regional Government Assets report quality.